How Does the State Restore Order During Crisis? Lessons From the U.K.'s Response to the "Riots" of August 2011. (March 2021) - Morrell, Kevin; Heracleous, Loizos; Fuller, Crispian; Bradford, Ben
We use speech act theory to study the U.K. state's response to large-scale public disorder across English cities in August 2011. This historical case has practical implications for understanding how nation states address other crises—because we explain in detail how the discourse of powerful state actors restores order. Drawing on parliamentary debate, Select Committee testimony, and interviews with police officers, our contribution is to describe and analyze how this happened contemporaneously at different levels. At street level, this involved the reassertion of sovereignty through territorial struggles by the police. At what we call "state level, " speech act theory helps us show how Members of Parliament framed the disorder and participants in ways that supported the reestablishment of norms and of order; principally through homogenization, in a process we describe as "tidying."